2017
DOI: 10.1017/ipm.2017.80
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of dementia among community dwelling older adults in receipt of state funded home care packages: implications for health care planning

Abstract: Objectives. The majority of people living with dementia in Ireland reside in their own homes, some supported by formal or informal home care. This audit aimed to estimate the prevalence of dementia and suspected cognitive impairment (CI) among older adults, 65+ years, in receipt of formal home care (domiciliary care) in a defined health service area in North Dublin. A secondary objective of the audit was to explore factors associated with dementia or CI in this cohort. Methods.A cross-sectional audit was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…In the present study, the prevalence of "cognitive dysfunction" was 43.1% consistent with our previous findings among home support recipients. 24 While there is generally a dearth of research on the prevalence of "cognitive dysfunction" among older people in receipt of home support, evidence from other countries (eg, Norway and Canada) suggests that people with "cognitive dysfunction" are relatively high users of home care services 30,31 In the present study, "cognitive dysfunction" was found to be significantly associated with LTC. There is a growing realisation of the importance of providing a rich and varied individualised set of responses to dependent older people with cognitive dysfunction, 11 many of which may be feasible to embed within home support.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…In the present study, the prevalence of "cognitive dysfunction" was 43.1% consistent with our previous findings among home support recipients. 24 While there is generally a dearth of research on the prevalence of "cognitive dysfunction" among older people in receipt of home support, evidence from other countries (eg, Norway and Canada) suggests that people with "cognitive dysfunction" are relatively high users of home care services 30,31 In the present study, "cognitive dysfunction" was found to be significantly associated with LTC. There is a growing realisation of the importance of providing a rich and varied individualised set of responses to dependent older people with cognitive dysfunction, 11 many of which may be feasible to embed within home support.…”
Section: Discussionmentioning
confidence: 57%
“…There is evidence that reduced activities of daily living (ADL) activity is associated with functional deterioration, LTC, and mortality among older people. 23,24 There have been no studies done on the identification of factors that influence admission to long-stay care in Ireland, or on predictors of mortality among community-dwelling older dependent adults. 20 In a systematic review and meta-analysis, Cepoiu-Martin et al found that increased age, functional impairment, behavioural, and psychological problems and being in the severe stages of dementia were significant predictors of LTC placement for people with dementia.…”
Section: Key Pointsmentioning
confidence: 99%
See 3 more Smart Citations